Chemical composition and antibacterial activity of Cymbopogon citratus and Cymbopogon flexuosus essential oils - Gonçalves, Maria Vanaina Souza; Silva, Luiz Everson da; Amaral, Wanderlei do; Quadros, Diomar Augusto de; Reis, Rodrigo Arantes; Amaral, Lucas Diovani Parabocz do; Garcia, Bruna; Deschamps, Cícero (Ciência e Natura, 2018)
Plant secondary metabolites have attracted considerable attention from the industry as consumers are increasing their interest for natural products over chemically synthesized reagents to be used as additives in food, cosmetics or pharmaceuticals. Some plant essential oils show significant antimicrobial properties and this could be exploited to produce new food preservatives or novel antimicrobial formulations. Here we describe the extraction, chemical analysis and antimicrobial properties of grass lemon Cymbopogon citratus and Cymbopogon flexuosus essential oils. Essential oils were extracted from dried leaves using hydrodestilation and their composition was established by gas chromatography coupled to mass spectrometry. Agar diffusion assays indicated that C. citratus and C. flexuosus essential oils act as antimicrobial agents against both gram negative and gram positive model organisms. These data support that lemon grass essential oils can be used as an alternative for microbiological control.